Stability of karyotype in serial isolates of Candida albicans from neutropenic patients. - Barton, R C (1995)
Serial isolates of Candida albicans were obtained from 20 patients with leukemia over periods of up to 8 months. The fingerprinting of these isolates by interrepeat PCR and random amplified polymorphic DNA PCR has been described previously (A. van Belkum, W. Melchers, B. E. de Pauw, S. Scherer, W. Quint, and J. F. Meis, J. Infect. Dis. 169:1062-1070, 1994). Contour-clamped homogeneous electric field gel electrophoresis was used to examine the chromosomes of these isolates. When changes in the karyotype were seen in a series of isolates, additional interrepeat PCR and Southern blotting with a repeat DNA sequence from the 27A family were performed. These two genotyping tools were used to determine if karyotypic changes seen in a series of isolates were due to chromosome rearrangements in a single strain or due to colonization with more than one strain. It was determined that changes in karyotype in a series of strains indicated infection by a new strain.